Bacteriostatic effects of phage F23s1 and its endolysin on Vibrio parahaemolyticus. (3rd June 2022) - Xia, Hai; Yang, Houji; Yan, Na; Hou, Wenfu; Wang, Huajuan; Wang, Xiaohong; Wang, Hongxun; Zhou, Min
Abstract: Vibrio parahaemolyticus is a common foodborne pathogenic bacterium and drug‐resistant strains are now widespread. Phages led by drug‐resistant V. parahaemolyticus strains are promising means to decrease the pressure on public health. We isolated a V. parahaemolyticus ‐specific bacteriophage F23s1 that was active at wide ranges of temperature (30–60°C) and pH (4–10). Phage F23s1 exhibited a specific host range; in that, only 13 of the 23 V. parahaemolyticus strains were lysed. F23s1 effectively inhibited the growth of V. parahaemolyticus strain F23 in shrimp at 25°C within 12 h at a multiplicity of infection of 1000. We sequenced the genome of phage F23s1 which comprised a 76, 648‐bp DNA with 105 open reading frames (ORFs) and identified an endolysin gene ORF52 that was then cloned and successfully expressed in Escherichia coli . The recombinant ORF52 protein significantly decreased OD600 nm of V. parahaemolyticus F23 from 0.978 to 0.249 when used at 20 µmol/L within 60 min. The endolysin also showed lytic activity against a panel of 23 drug‐resistant V. parahaemolyticus and 12 Salmonella strains with a higher lytic ability for V. parahaemolyticus . The phage F23s1 and its endolysin will be useful for preventing and controlling V. parahaemolyticus in food safety.